An Unusual Case of Unilateral Pulmonary Edema With Contralateral Bronchial Obstruction. (May 2015) - Jambeih, Rami; Brown, Brent R.; Huard, David R.; Naqvi, Syed
Abstract : Abstract: A 61 year-old man presented with progressive shortness of breath. Computed tomography scan of the chest showed diffuse ground glass infiltrates and dilated pulmonary vessels in the right lung in addition to bilateral pulmonary masses with obstruction of the left main pulmonary bronchus. The patient underwent bronchoscopy with destruction of the tumor obstructing the left main pulmonary bronchus, resulting in clinical improvement and resolution of the right pulmonary infiltrates. We hypothesize that the patient developed right pulmonary edema secondary to hypoxic vasoconstriction of the left lung. This case suggests a rare mechanism of unilateral pulmonary edema and supports inclusion of pulmonary edema in the differential diagnosis of unilateral pulmonary infiltrates in the setting of contralateral bronchial obstruction.